Women And Sustainability Of Seaweed Farming In Southeast Sulawesi - Wa Ode Sifatu (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to look at the role of women in the sustainability of seaweed farming in Southeast Sulawesi. The theory for reading research data is Foucault's thinking about power with ethnographic methods. Women have the ability as individual capacities in society. Women work hard to build stable community life. The double burden of women as household managers and seaweed farmers does not become a barrier to creativity. Openness between men and women about what is and is not allowed outside of nature does not apply to seaweed farming. Women's initiatives are often ignored and receive less attention in policymaking. Women can criticize the knowledge of agricultural instructors—women as key actors in the sustainability of seaweed farming. The attitude of openness in the household to be optimally improved. Women as valuable assets need to be continuously explored and forged for development needs.